THE INFLUENCE OF HUMAN RESOURCE COMPETENCE ON THE PERFORMANCE OF EMPLOYEES OF THE INDUSTRIAL AND TRADE COOPERATIVE TRADE OF ENREKANG REGENCY - Uhud Darmawan Natsir; Sithy Nur Aisyah; Rezky Amalia Hamka; Romansyah Sahabuddin; Tenri Sayu Puspitaningsih Dipoatmodjo (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This research was to know the effect of human resource competence (HR) on employee performance at the Industry and Trade Cooperative of Enrekang Regency. HR competence is the independent variable in this study and employee performance is the dependent variable. The type of research used is quantitative. The population as well as the research sample were 33 employees of the Industry and Trade Cooperative of Enrekang Regency. The data collection technique was carried out through a Likert scale-based questionnaire distributed to respondents. The data analysis technique used simple linear regression analysis with the help of Statistical Product and Service Solutions (SPSS) software version 26. The results showed that HR competence had a significant positive effect on employee performance with a determination efficiency value (R Square) of 54.7%, while the remaining 45.3% was influenced by other variables outside this study.